Lipschitz behavior of solutions to nonconvex semi-infinite vector optimization problems - Huy, N. Q.; Kim, D. S. (Journal of global optimization, 2013)
This paper is devoted to developing new applications from the limiting subdifferential in nonsmooth optimization and variational analysis to the study of the Lipschitz behavior of the Pareto solution maps in parametric nonconvex semi-infinite vector optimization problems (SIVO for brevity). We establish sufficient conditions for the Aubin Lipschitz-like property of the Pareto solution maps of SIVO under perturbations of both the objective function and constraints.